Isotopes Applications in Earth Sciences - Abdel Rahman, Rehab O. (IntechOpen, 2020)
Applications of stable and radioactive isotopes are supporting sustainable development goals. They are used to study different ecological, biological, chemical and geological systems and understand their dynamics and interactions. Environmental applications of these isotopes include tracing pollutant migration, assessing and predicting climatic changes and planning for water management. This book highlights recent isotope applications in studying the hydrosphere and lithosphere compartments of the Earth. These applications include the use of natural and anthropogenic isotopes to understand the natural processes in these compartments. Chapters focus on soil distribution and sedimentation, dating tectono-metamorphic events, assessing brine origin, planning for water management and the effect of variation of environmental conditions on the biological and isotopic changes in coral skeletons.